Control By the Host State: Peranan Hukum Dalam Kegiatan Penanaman Modal Asing - Christian, Ando Gidion (Universitas Sang Bumi Ruwa Jurai, 2024)
Foreign Direct Investment plays a crucial role in the global economy, facilitating the flow of capital, technology, and expertise across national borders. As foreign direct investment increases, host countries have sought to assert greater control over these investments to safeguard their national interests and maximize economic benefits. This paper provides a comprehensive overview of the topic of control by Republic of Indonesia in its capacity as host state in foreign direct investment. It explores the various policy measures implemented by Republic of Indonesia to exert control, examines the motivations behind these measures, and analyses the implications for both Republic of Indonesia and foreign investors. The findings highlight the complex dynamics and trade-offs involved in controlling foreign direct investment, emphasizing the need for a balanced approach that ensures host state interests without discouraging foreign investment within the jurisdiction of Republic of Indonesia